The Fallout of 9/11 on Asian Economies: Policy Options - Pandey, Ravindra Prasad (NRB Economic Review, 2004)
As a result of the September 11, 2001 terrorist attacks on the United States, the immediate reaction of various economists around the globe was that the Asian economies, in particular the Southeast Asian economies, would deepen, leaving no room for an early rebound from the 1997 financial crisis. However, as events developed, the global as well as the regional economic developments gave way for greater optimism towards the immediate economic prospects of these countries. The disruption of the economy following the attacks turned out to be less disruptive than originally thought as statistics show distinct signs of improvement in the global economic situation. In the regional front, most regional stock markets rallied and consumer confidence improved, boosting domestic demand. The result of the unprecedented fiscal measures and monetary stimulus such as cuts in interest rates, income tax cuts, and post-attack government spending led to the mild rebound strengthening to more or less a full-blown economic recovery since the later part of 2002.The trend continues even at a faster pace. In nutshell, the completion of completion of initiated reform agenda and maintenance of strong economic fundamentals will provide necessary policy options for the countries in the event of uncertainty in the global recovery.